Livestock prices volatility analysis: implications for the implementation of a futures and option market in Uruguay - Gutiérrez, G.; Caputi, P. (Agrociencia Uruguay, 2004)
Current paper is intended to analyze price volatility of the livestock sector in Uruguay in order to allow both, farmers and slaughter house industry, to manage efficiently price risk fluctuations. Feasibility of future markets depends basically on the existence of a large spot market, of fluctuations on supply and demand functions, the number of participants on this market, lack of other intervention mechanisms in the livestock market that could affect market efficiency, and price volatility, Uruguay had futures market on livestock but it was unable to sustain itself because of lack of interest from the local industry as well as a poor contract design. it was analyzed the structure of the beef agro industrial chain with special interest on the market structure as well as the behavior of livestock prices during large time periods. In general terms there is no evident restrictions for the implementation of a futures and options market for livestock in Uruguay since current conditions of the spot market are sufficient. Price volatility, measured on a weekly basis, is similar to related products traded in the international market. a futures contract is proposed based on an index structure that represents accurately domestic slaughter.